The fundamentals of boosting high-quality development by megaprojects: A systematic literature review - Ying Han; Qing Yang; Pingye Tian (Project Leadership and Society)
High-quality development is a new concept to promote social and economic development initiated by China in 2017, which originates from sustainable development but is more comprehensive. Using the systematic literature review method, this paper explores the evolution, core aspects and role of megaprojects in boosting high-quality development. Firstly, by building keyword co-occurrence networks, this paper discusses the evolution and core topics of megaproject management research from three dimensions: time, research field, and region. Secondly, this paper develops a theoretical model outlining the fundamentals of boosting high-quality development by megaprojects, which contains five aspects of high-quality development (i.e., economy, society, environment, innovation and safety). Further, we propose a value assessment framework of boosting high-quality development by megaprojects, which accounting for the megaprojects’ life cycle process and deliverables. Finally, this paper discusses future trends of megaprojects boosting high-quality development. By examining these key fields, the paper offers valuable insights into the transformative potential of megaprojects in boosting high-quality development and their practical implications.